Ni(COD)(DMFU): A Heteroleptic 16-Electron Precatalyst for 1,2-Diarylation of Alkenes - Kim, Nana; Tran, Van T.; Apolinar, Omar; Wisniewski, Steven R.; Eastgate, Martin D.; Engle, Keary M. (Synlett, 2021)
Electron-deficient olefin (EDO) ligands are known to promote a variety of nickel-catalyzed cross-coupling reactions, presumably by accelerating the reductive elimination step and preventing undesired β-hydride elimination. While there is a growing body of experimental and computational evidence elucidating the beneficial effects of EDO ligands, significant gaps remain in our understanding of the underlying coordination chemistry of the Ni–EDO species involved. In particular, most procedures rely on in situ assembly of the active catalyst, and there is a paucity of preligated Ni–EDO precatalysts. Herein, we investigate the 16-electron, heteroleptic nickel complex, Ni(COD)(DMFU), and examine the performance of this complex as a precatalyst in 1,2-diarylation of alkenes.
Keywords: nickel; precatalysts; homogeneous catalysis; electron-deficient olefin ligand